BENTUK PENYAJIAN TARI GATOT KOCO SEKAR PADA MASYARAKAT JAWA MEDAN HELVETIA - FATMA ZUL AIKA (Gesture: Jurnal Seni Tari, 2014)
ABSTRACT In addition to the existing ethnicities in North Sumatera, namely Malay, Batak Toba, Sibolga, Mandailing, Dairi, Simalungun, Karo and Nias.Including ethnic Javanese migrants who have been around a long time in North Sumatera. When the Dutch colonial era, including the island that has the densest communities in Indonesia. Because numerous and densely populated, the Dutch colonial dissemination / transmigration population to minimize the number of people on the island of Java to some islands that are considered population is still small. The rational for keeping the exixting plantations in the spread of the population.Then one of the islan of Java, namely the distribution of the population on the island of Sumatera.